EFFECT OF DIFFERENT LEVELS OF P AND K ON GROWTH, FORAGE YIELD AND QUALITY OF CLUSTER BEAN (C YAMOPSIS TETRAGONOLOBUS L.) - M. Ayub; M. A. Nadeem; M. Naeem; M. Tahir; M. Tariq; W. Ahmad (Journal of Animal and Plant Sciences, 2012)
A field experiment was conducted to investigate the effect of different P and K levels on forage yield and quality parameters of cluster bean at the Agronomic Research Area, University of Agriculture, Faisalabad during the growing period of 2007. The phosphorus and potassium were applied in eight different combinations i.e. 0-0 (T1), 25-0 (T2), 25-25 (T3), 40-40 (T4), 55-55 (T5), 70-70 (T6), 85-85 (T7) and 100-100 (T8) kg ha-1. The results revealed that above ground plant biomass like plant height, stem diameter, number of branches and leaf area per plant and measures of nutritional profile like crude protein, crude fibre and ash contents were significantly improved with PK application over control. The PK application at the rate of 70-70 kg ha-1 registered the highest value for plant height and stem diameter. Whereas, the maximum number of branches and leaf area per plant, fresh and dry matter yield was achieved with 85-85 kg PK ha-1. Among the forage quality traits, the dry matter % age was not responsive to PK application. The highest crude fibre and ash contents in plant dry matter was produced with 100-100 kg PK ha-1. The crude protein contents showed a steady increase in crude protein up to 85-85 kg PK ha -1 and further increase in PK fertilizer significantly  reduced crude protein. For obtaining high yield with good nutritional value, PK fertilizer must be applied at the rate of 85-85 kg ha -1 under the irrigated conditions of Faisalabad.
Keywords: Phosphorus; potassium; forage yield; quality; cluster bean